2016
DOI: 10.1186/s13638-016-0640-2
|View full text |Cite
|
Sign up to set email alerts
|

Two-way decode-and-forward cooperative systems with signal space diversity

Abstract: In this paper, a novel scheme is proposed to enhance the spectral efficiency of a two-way cooperative relaying system, where two source terminals exchange information directly and via K intermediate relays using the three-phase two-way decode-and-forward (DF) protocol. Signal space diversity (SSD) is incorporated into the two-way cooperative relaying system in the proposed scheme that exploits the inherent diversity in the modulation signal space by rotating and expanding the ordinary constellation. The propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 39 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The concept of micro takaful is said to be close to takaful. Khan (2010) defines micro takaful as "a mechanism to provide Sharia-based protection to disadvantaged blue-collar workers at a reasonable cost". Micro-takaful is designed as a protection program for low-income people and the product can be delivered to them with some modifications (Amin., 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept of micro takaful is said to be close to takaful. Khan (2010) defines micro takaful as "a mechanism to provide Sharia-based protection to disadvantaged blue-collar workers at a reasonable cost". Micro-takaful is designed as a protection program for low-income people and the product can be delivered to them with some modifications (Amin., 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proposed scheme is shown to enhance both the spectral efficiency and reliability. In another work [20], following the scheme in [17], a multi-relay TWRC employing DF based SSD is presented. Again it has been shown that performance and spectral efficiency are enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…3 for relay phase, since both the power distribution schemes in Figs. 2 and 3 are with the computational complexity of O (1). In a Nsubcarrier two-way relay OFDM system, there are 2 N possible subchannel allocations, so the complexity of the optimal resource allocation based on exhaustive search is O 2 N .…”
Section: Complexity Analysis and Equivalent Problem Extension 431 Cmentioning
confidence: 99%